Associations between the practice of bullying and individual and contextual variables from the aggressors' perspective - Wanderlei Abadio de Oliveira; Marta Angélica Iossi Silva; Jorge Luiz da Silva; Flávia Carvalho Malta de Mello; Rogério Ruscitto do Prado; Deborah Carvalho Malta (Brazilian Society of Pediatrics, 2016)
Objectives: Estimating the prevalence of bullying among Brazilian students from the perspective of the aggressor and analyzing its association with individual and context variables. Methods: Cross‐sectional population‐based study conducted with data from the National Survey on Student Health. A total of 109,104 students attending the 8th grade in public and private schools were included. Data were collected through a self‐applied questionnaire. A model of association between bullying and variables in the following domains was tested: sociodemographics, risk behaviors, mental health, and family context. Univariate and multivariate analyses were also performed. Results: The prevalence of aggressors in bullying situations was 20.8%. The following variables remained associated in the final multivariate model: being a male (OR: 1.87; CI 95%: 1.79‐1.94), 16 year‐old students were the least frequently associated with bullying (OR: 0.66; IC 95%: 0.53‐0.82), students from private schools (OR 1.33 IC95% 1.27‐1.39). Most aggressors reported feeling lonely (OR: 1.22; IC 95%: 1.16‐1.28) and episodes of insomnia (OR: 1.21; IC 95%: 1.14‐1.29), and a high prevalence of physical violence in the family (OR: 1.97 IC 95%: 1.87‐2.08). The aggressors miss classes more frequently (OR: 1.45; IC 95%: 1.40‐1.51), regularly smoke more (OR: 1.21; IC 95%: 1.12‐1.31), consume alcohol (OR: 1.85; IC 95%: 1.77‐1.92) and illegal drugs (OR: 1.91; IC 95%: 1.79‐2.04), regularly practice sex (OR: 1.49 IC95% 1.43‐1.55), and exercise (OR1.20 IC95% 1.16‐1.25). Conclusions: Data indicate that bullying is an important aspect that interferes in the learning‐teaching process and in the health of students.